Ekoteologitani untuk Kedaulatan Pangan Etos Islam dan Spirit Bertani pada Masyarakat Desa Srimartani, Kecamatan Piyungan, Bantul, Yogyakarta - Soehadha, Moh. (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2017)
This article presents the results of an explorative research that examined the concept of agrarian ecotheology. This issue was raised with the assumption that Islamic teachings can be a part in the restrengthening of agrarian culture i.e. to take part in enhancing food sovereignty and security in Indonesia. This study is established on the perspective of anthropological ecology. The data source for this article is results of research that has been conducted at the Srimartani Village, Piyungan District, Bantul Regency, Yogyakarta Special Region Province. Data collection was conducted by using various techniques such as participant observation, focused group discussion (FGD) and interviews through questionnaires. The data collected from the field research was then analyzed using a descriptive-interpretative method. The study results show that Islamic teachings could be employed in restrengthening the agrarian culture, that is as a means to enhance food sovereignty and security. This study also provides critical contribution to the perspective of contemporary Islamic ecotheology so that it does not tend to be anthropocentric, thus becoming exploitative in nature. A new construction of Islamic ecotheology, which accommodates the view that humans, as farmers as well, have a proportional position within their environment, needs to be developed.